2001
DOI: 10.1016/s0002-9440(10)61703-8
|View full text |Cite
|
Sign up to set email alerts
|

Transgenic Expression of Cyclin-Dependent Kinase 4 Results in Epidermal Hyperplasia, Hypertrophy, and Severe Dermal Fibrosis

Abstract: In a previous report we have described the effects of expression of D-type cyclins in epithelial tissues of transgenic mice. To study the involvement of the Dtype cyclin partner cyclin-dependent kinase 4 (CDK4) in epithelial growth and differentiation, transgenic mice were generated carrying the CDK4 gene under the control of a keratin 5 promoter. As expected, transgenic mice showed expression of CDK4 in the epidermal basal-cell layer. Epidermal proliferation increased dramatically and basal cell hyperplasia a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

9
56
0
1

Year Published

2002
2002
2022
2022

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 35 publications
(66 citation statements)
references
References 48 publications
9
56
0
1
Order By: Relevance
“…We have previously described the phenotypical consequences of forced expression of hCDK4 under the K5 promoter (K5CDK4 mice; ref. 13). Similarly, overexpression of hCDK2 under the K5 promoter also drives the expression to stratified epithelium (our unpublished results).…”
Section: Resultssupporting
confidence: 58%
See 2 more Smart Citations
“…We have previously described the phenotypical consequences of forced expression of hCDK4 under the K5 promoter (K5CDK4 mice; ref. 13). Similarly, overexpression of hCDK2 under the K5 promoter also drives the expression to stratified epithelium (our unpublished results).…”
Section: Resultssupporting
confidence: 58%
“…6C, lane 6). We previously established that increased expression of CDK4 results in the activation of CDK2 through a mechanism involving sequestration of p21 Cip1 and p27 Kip1 in epithelial tissues (13,24), thus, we also assayed CDK2 kinase activity in pituitary lysates. Pituitary lysates from p27 À/À and K5CDK4/p27 À/À mice show strong CDK2 kinase activity compared with wild-type and K5CDK4 mice (Fig.…”
Section: Cancer Researchmentioning
confidence: 99%
See 1 more Smart Citation
“…Therefore, we have used the mouse skin two-stage carcinogenesis model as an experimental approach to determine how CDK4 overexpression influences tumor development. We used the previously described K5-CDK4 transgenic lines that showed 2.5-fold (K5-CDK4-2305) and 7.5-fold (K5-CDK4-2303) increased expression of CDK4 in the basal cell layer of epidermis (Miliani de Marval et al, 2001). The dorsal skin of K5-CDK4 transgenic mice and wildtype littermates were topically treated with a subcarcinogenic dose of the genotoxic carcinogen DMBA and later promoted with the phorbol ester TPA.…”
Section: Cdk4 Overexpression Results In Enhanced Malignant Progressionmentioning
confidence: 99%
“…We have previously reported that forced expression of CDK4 in mouse epidermis led to phenotypic abnormalities, such as hyperplasia and hypertrophy and severe dermal fibrosis (Miliani de Marval et al, 2001). Here, we have investigated the susceptibility to chemically induced skin tumor formation.…”
Section: Introductionmentioning
confidence: 99%